Performance Comparison of Host Identity Protocol and TCP/IP with Firewall against Denial of Services - Alfan Presekal; Riri Fitri Sari (Institute of Advanced Engineering and Science, 2014)
Host Identity Protocol (HIP) is a new kind of Internet protocol which has been developed to resolve the existing problems of Internet protocol TCP/IP. As a new protocol HIP provides many advantages compared to TCP/IP such as in the aspect of security and mobility. Unfortunately, the deployability rate of HIP was still low. One of the reason is because particular solution for currently Internet problems already popular and deployed worldwide. In this work we compare the performance of HIP and TCP/IP using several scenarios. Simulations result show that TCP response time in normal condition (zero attack condition) 98,627 ms, while HIP has the response time of 99,711 ms. We also compare the performance of the HIP, TCP/IP, and SSL against the low to medium Denial of Services attack (DoS). In the condition of low to medium DoS attack, the order from best performance are TCP/IP, HIP, and then the worst one is SSL. In the condition of high DoS attack three of them TCP/IP, SSL, and HIP cannot work. Only HIP that implement HIP Firewall with authorization scenarios that are still available for service.